Seismic Behavior of Posttensioned Concrete Bridge Piers with External Viscoelastic Dampers - Anxin Guo; Huixing Gao (Shock and Vibration)
This paper investigates the seismic performance of posttensioned concrete piers with external viscoelastic dampers to improve the energy dissipation capacity of this type of structure. An installation scheme for viscoelastic dampers on bridge piers is proposed, and the mechanical models of the damper are analyzed according to the installation scheme. By attaching the viscoelastic dampers to the posttensioned bridge piers, the analytical model of the hybrid system is established using the OpenSees finite element analysis package. Cyclic behavior and time history analyses are conducted on a posttensioned bridge with and without viscoelastic dampers using the established finite element model. The analysis results indicate that the viscoelastic dampers can effectively improve the seismic performance of the bridge structures with posttensioned piers.